An update on Zika virus infection. Issue 10107 (4th November 2017) - Baud, David; Gubler, Duane J; Schaub, Bruno; Lanteri, Marion C; Musso, Didier
Summary: The epidemic history of Zika virus began in 2007, with its emergence in Yap Island in the western Pacific, followed in 2013–14 by a larger epidemic in French Polynesia, south Pacific, where the first severe complications and non-vector-borne transmission of the virus were reported. Zika virus emerged in Brazil in 2015 and was declared a national public health emergency after local researchers and physicians reported an increase in microcephaly cases. In 2016, WHO declared the recent cluster of microcephaly cases and other neurological disorders reported in Brazil a global public health emergency. Similar clusters of microcephaly cases were also observed retrospectively in French Polynesia in 2014. In 2015–16, Zika virus continued its spread to cause outbreaks in the Americas and the Pacific, and the first outbreaks were reported in continental USA, Africa, and southeast Asia. Non-vector-borne transmission was confirmed and Zika virus was established as a cause of severe neurological complications in fetuses, neonates, and adults. This Review focuses on important updates and gaps in the knowledge of Zika virus as of early 2017.